Prevalence and risk factors of bovine schistosomiasis in Northwestern Ethiopia - Yihunie, Abebe (BMC Vet Res, 2019)
BACKGROUND: Parasitic diseases remain major bottle neck to livestock development in developing nations. The objective of this study was to determine the prevalence and associated risk factors of Bovine Schistosomiasis (BS) in South Achefer District, northwestern Ethiopia. METHODS: A cross-sectional copro-parasitological and observational study was conducted in South Achefer district from October, 2015 to April, 2016. Faecal samples were collected from 360 randomly selected cattle for coprological examination of Schistosoma eggs using sedimentation technique. The geographical origin (kebele), signalment (breed, sex and age) and body condition of study animals were recorded as independent variables. RESULTS: Of the total of 360 faecal samples examined, 80 (22.2%) were found positive for Schistosoma bovis eggs. Prevalence of BS showed significant variability amongst study kebele’s (p = 0.000) as well as between different breeds (p = 0.009), sexes (p = 0.030) and body condition groups (p = 0.000) of study animals. Compared to Gedema kebele, risk of Schistosomia bovis infection was significantly higher (p < 0.05) in Ahurie kebele (95% CI OR, 1.497–6.680) and lower in Kar kebele (95% CI OR, 0.069–0.507). Meanwhile, risk of BS was significantly higher in cattle with poor body condition (95% CI OR, 3.171–15.652) as compared to that exhibiting good body condition. Local breed (95% CI OR, 1.282–5.102) and female (95% CI OR, 1.018–3.634) cattle showed considerably higher risk of infection than crossbred and male cattle, respectively. CONCLUSION: Overall, agro-ecological, genotypic and sexual factors were important in determining prevalence of BS which had negative association with the nutritional status of cattle. Current and parallel prior observations underscore a need for careful consideration of the disease and its epidemiological drivers in genetic improvement programs and routine health management practices.